Poverty in Hopley area: a myth or reality - Kuvheya, Prudence Brenda (Midlands State University, 2021)
The study sought to bring out the reality or the mythical concept that surrounds the issues of poverty in Hopley settlement. Hopley settlement is an informal settlement that was established after the Operation Murambatsvina (Restore Order) that was instigated by the Government of Zimbabwe in the year 2005. According to the GoZ the operation was meant to restore order in the cities that have been ravaged by illegal activities as well as containing the rife of crime rate. However according to political analysts, the infomous operation had some political conotations that sorrounded it. The basic needs approach defines poverty as the scarcity of resources and opportunities to satisfy basic needs. The study focused on assessing the causes of poverty, manifestations of the epindemic as well as the copying strategies that are particular to the area of study Hopley settlement. With the continued economic meltdown in the country, socio-economic status at community and household levels have been further dismantled and the propects of the current Zim asset have not been delivered thus motivating the study. The research used the qualitative research designs in which questionnaires, interviews, non-probability sampling as well as observation were empolyed to gain information. The study found out that Africa as a whole experiences poverty and the causes affecting the continent also infringe on the community and household livelihoods, however there are particular causes of poverty that are attached to the area of study which include the Operatiom Murambatsvina, Exclusion as well as no land rights. The research again found out that poverty manifest in different ways and these manifestations vary with area or rather geographical location and income rates. Nevertheless poverty in Hopley area has resulted in more school dropouts, domestic violence, malnutrition, high crime rates as well as indecent housing. These have affected livelihoods to a greater extent and it is likely that a culture of poverty might be created. Also the study found out that there are various copying strategies that have been employed so as to curtail poverty. These include offering cusual labour, motor repaires, school dropout, migration as well as remittances among others. The researcher also recommends collective action whereby different stakeholders like the GoZ and Harare City Council should harness ideas together with the people direcly affected so as to deal with poverty and bring sustainable development. A plan on upgrading slums should be iniated so as to develop these settlement that are housing almost a third of city dwellers. Further studies could be done by looking at the prospects of previous national policies in trying to deal with urban poverty and in particular poverty in the informal settlement.